Analisis Bibliometrik Tentang Quiet Quitting - Ario Bagus Nugroho; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Performance and engagement of the working employee could drop anytime, the company’s inability to provide work-life balance could even lead to quiet quitting that if ignored could increase employee turnover. The purpose of this study is to notice and to give information about the connections about quiet quitting based on previous studies. The methods used for this bibliometric analysis study are to merge the use of Publish or perish software to find previous studies with keyword “quiet quitting” and the use of VOSviewer software to cluster and to visualize its items. The results of this study are in the span of 2022-2024 there are 996 studies about quiet quitting, VOSviewer cluster the items of study into 5 (five) cluster and visualize the connection between items of study, publication year, and topic density or publication frequencies. The visualizations results show that these items of study have connections between clusters, these items of study are quiet firing and disengagement both have a connection of their own, the next items of study are the great resignation, management, work-life balance and job burnout each items have a connection with items of study job satisfaction. This study also find that items of study job burnout and job satisfaction are the items which have relatively small density because it is mostly studied in the year of 2024. Based on this study can be concluded that the connection between items of study quiet firing and disengagement are worth paying attention to whenever discussing quiet quitting also items of study job burnout and job satisfaction are the items which connections on quiet quitting are rarely studied.